A Modified Key Generation Algorithm to Rebalanced-RSA and RPower-RSA - İsrafil Okumuş; Ercan Celık (MANAS: Journal of Engineering)
This paper presents a novel key generation algorithm for Rebalanced-RSA and RPower-RSA that accelerates encryption and decryption processes by utilizing smaller modular exponents. Subsequently, two of these variants are modified by altering the key generation process. A theoretical analysis of all variants, including the proposed modifications, demonstrates that these key generation algorithms improve the encryption process compared to the original variants, and since the encryption key size and one of the decryption key sizes are approximately equal in length, they achieve a more balanced computational effort between encryption and decryption.